ARUS PEMBARUAN PENDIDIKAN ISLAM DI NUSANTARA: ANALISIS KONTRIBUSI KRITIS PARA PEMIKIR PENDIDIKAN ISLAM INDONESIA ERA MODERN - Nur Lailiyah Ramadhani; Silan Hiffi Rahmadani; Nur Apriyanto; Ririn Dwi Wiresti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyze Islamic education reform in the Indonesian archipelago and the contributions of Indonesian Islamic educational thought in responding to social change and modern challenges. Using a qualitative library research approach, data were collected from relevant books and scholarly articles and analyzed through content and comparative analysis. The findings indicate that Islamic education reform has developed gradually through a dialectical process between the preservation of classical traditions and the demands of modernity, reflected in institutional reform, the integration of religious and general sciences, and the reconstruction of educational paradigms. Indonesian Islamic educational thought demonstrates a continuous reform trajectory, moving from the reinforcement of moral values toward systemic reform and epistemological integration grounded in Islamic principles. The novelty of this study lies in its positioning of Islamic education reform as an evolutionary and complementary process rather than a dichotomy between tradition and modernity, highlighting its relevance for developing an integrative, moderate, and globally adaptive Islamic education framework.